Réponses

2013-04-16T14:30:38+02:00

a) 3p(p-1)-(2p+3)² = 3p²-3p-(4p²+12p+9) = 3p²-3p-4p²+12p+9 = -p²+9p+9= -p²+9(p+1)

 

b) x+y=200

    70x+40y=10 400

 

    -70x-70y=-14 000

      70x-40y=10 400

 

    -110y= -3600 ; d'ou y= 3600/110= 360/11

 

Et pour trouver x, tu remplace y par 360/11 dans tes equa du systeme

 

2013-04-16T15:24:41+02:00

3P²-3P-( 4p²+12p +9)

= 3p²-3p-4p²-12p-9

= -p²-15p-9

 

x +y = 200

70x +40y = 10400

 

-40x -40y = --8000

70x +40y = 10400

 

30x = 2400

x = 2400/30 = 80